Effective Polarization Filtering Techniques for Ground Penetrating Radar Applications - Wirth, Sebastian (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.Ground penetrating radar (GPR) is increasingly being used for landmine detection. In contrast to metal detecting, GPR can be used for detection of low-metal content or non-metal content targets. Subsurface radar still suffers from two typical problems, a strong clutter response from the surface and high signal to clutter levels in the underground. This paper addresses these problems through the use of a novel near-field full-polarimetric (0.4-5.0GHz) SFCW GPR system that measures the polarimetric microwave backscatter response and synthesises an equivalent complex clutter scattering matrix that suppresses subsurface clutter in the co-pol and cross-pol channels. The technique is compared to Stokes parameter analysis of the polarimtric response and found to offer comparable or better clutter suppression imagery. Results for these techniques are presented for raw B-scan GPR images and synthetic aperture radar imagery. Significant signal features for various buried objects are also characterised. These include GPR near-field radar cross sections for some landmines and common clutter targets and the unique polarization signatures of these objects that can be used to both discriminate and potentially identify unknown landmines. The paper also describes the polarisation channel equalisation and quasi-bistatic antenna calibration procedure undertaken to acquire accurate imagery and absolute RCS values. The presented GPR system uses a linear polarised TEM horn as transmit antenna and two near-field probe (loop) antennas, arranged orthogonally and in front of the TEM horn, to collect the co- and cross-polar response. The loop antennas are placed just outside the near-field of the TEM horn at 11 cm in front of the aperture at 400 MHz. The antenna configuration is moved over a 3m sandpit mechanically. The sandpit is comprised of three bays that each are filled with different soil types (sand, sand/gravel mix and loam) and the presented clutter suppression techniques are tested for targets buried in these different soils with different moisture levels.
Keywords: 'Ground-penetrating-radar'; 'Full polarimetry'; 'TEM horn antenna'; 'DSDS18 poster'; 'DSDS18'; 'Antennas and Propagation'; 'Photogrammetry and Remote Sensing'